MARTIN HEIDEGGER ON INAUTHENTIC EXISTENCE: THE NIGERIAN PERSPECTIVE - ThankGod Bekweri Amadi; Sotonye Big- Alabo (PT. Antis International Publisher, 2026)
Objective: Nigeria currently faces a profound crisis of identity and sustainable development, characterized by widespread inauthenticity across its societal and individual spheres. This is more glaring in the political economy of the nation in terms of her adaptation of foreign-related, non-viable development pathways and the increasing fleeing of her citizens, especially the youths, which is popularly referred to as the Japa syndrome. The deep philosophy of Martin Heidegger supplies a moving context for understanding this complex dilemma — particularly the notion of inauthentic existence (Das Man), in which individuals immerse themselves in the indistinct crowd, giving up their unique identity and their ability to act authentically and autonomously. To achieve this, our objectives are twofold: first, to thoroughly delineate Heidegger’s understanding of inauthenticity; and second, to critically analyze how Nigeria's unsustainable development patterns and the urgent